The Effect of Return On Assets and Return On Equity To Earning Per Share and Price Book Value In Sub-Sectors of Construction Companies Listed In Indonesia Stock Exchange In 2015-2018 - Shofi Malina; I Gede Arimbawa; Ani Wulandari (Yayasan Ahmar Cendekia Indonesia, 2020)
The purpose of the research is to analyze the effect of return on assets and return on equity on earnings per share and price book value in building construction sub sector companies listed on the Indonesia Stock Exchange in 2015-2018. The population of this research was the building construction companies listed on the Indonesia Stock Exchange during 2015-2018. The sample used was 10 construction companies with a purposive sampling method. Data collection techniques used in the documentation were in the form of secondary data and library research. The analysis was using path analysis. It was revealed that the return on assets has a significant negative effect and return on equity have a significant positive effect on earnings per share. While return on equity has a significant positive effect and earnings per share has a significant negative impact on price book value. However, return on assets does not have a significant effect on price book value.